2018
DOI: 10.1590/0102-311x00206116
|View full text |Cite
|
Sign up to set email alerts
|

Advanced maternal age and its association with placenta praevia and placental abruption: a meta-analysis

Abstract: This study aimed to investigate the existence and magnitude of the association between advanced maternal age (AMA) and occurrence of placenta praevia (PP) and placental abruption (PA) among nulliparous and multiparous women, by a systematic review and meta-analysis. We searched articles published between January 1, 2005 and December 31, 2015, in any language, in the following databases: PubMed, Scopus, Web of Science, and LILACS. Women were grouped into two age categories: up to 34 years old and 35 years or ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 40 publications
3
26
0
3
Order By: Relevance
“…Even after adjustment for confounding factors, such as previous c-section, parity, smoking and use of ART, these differences remained significant.In the FATER trial, Cleary-Goldman et al [7] found a similar risk of placenta previa (AdjOR 2.8 at > 40 years) in a prospective study among more than 36000 patients. This association has also been described in a recent meta-analysis [32], although a main limitation was the lack of adjustment for confounding factors.…”
Section: Discussionsupporting
confidence: 72%
“…Even after adjustment for confounding factors, such as previous c-section, parity, smoking and use of ART, these differences remained significant.In the FATER trial, Cleary-Goldman et al [7] found a similar risk of placenta previa (AdjOR 2.8 at > 40 years) in a prospective study among more than 36000 patients. This association has also been described in a recent meta-analysis [32], although a main limitation was the lack of adjustment for confounding factors.…”
Section: Discussionsupporting
confidence: 72%
“…A systematic review by Martinelli et al found similar results, even after stratifying for parity. The authors suggest that atherosclerotic changes in the blood vessels may impair the flow and infarction as underlying causes, which may provoke a lower implant of the placenta in the uterine cavity [39]. Regarding fetal presentation, we found a non-vertex presentation of the fetus in 4,2% of women younger than 20 years and 5,7% in 40+ -year-old women.…”
Section: Discussionmentioning
confidence: 68%
“…Despite an abundance of data presented in narrative reviews regarding a general decline in successful ART procedures with advancing age, there is some lack of concrete data which would allow a robust conclusion to be drawn regarding a specific cut-off point at which critical decisions might be made for management of patients in the AMA category. This discrepancy of evidence is attributed to the fact that the majority of published studies compares cohorts of patients employing "age boxes" described by a large range in age frames between 30 and 35, 35 and 39 or above 40 [3][4][5]8,19,21,25].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of published data suggests that AMA exerts a negative impact on pregnancy outcomes accompanied with poor prognosis, both of which are associated with a variety of complications during both the gestational and delivery stage [3][4][5][6][7][8][9][10]. In addition, women over 35 report poorer results during In Vitro Fertilization (IVF) treatment due to inadequate ovarian stimulation as well as a lower embryo implantation rate [11,12].…”
Section: Introductionmentioning
confidence: 99%